2021
DOI: 10.1016/j.diagmicrobio.2021.115426
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of COVID-19 for a Clinical Microbiology Department

Abstract: Objectives To quantify the workload and cost overload that the COVID-19 pandemic has meant for a Clinical Microbiology laboratory in a real-life scenario. Methods We compared the number of samples received, their distribution, the human resources, and the budget of a Microbiology laboratory in the COVID pandemic (March-December 2020) with the same months of the previous year. Results the total number of samples processed in the Clinical Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Moreover, because prior studies have shown that central line-associated infection is a common cause of BSIs in patients with COVID-19, a fear of prolonged patient contact, the practice of pronation for ventilated patients [18], and aerosolization of SARS-CoV-2 could be a barrier to catheter hygiene and maintenance [7]. Finally, the pandemic has revealed staffing constraints and supply chain weaknesses that limit the ability of microbiology labs and infectious disease specialists to fully support infection prevention and antimicrobial stewardship policies, which also may affect BSI rates and outcomes [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because prior studies have shown that central line-associated infection is a common cause of BSIs in patients with COVID-19, a fear of prolonged patient contact, the practice of pronation for ventilated patients [18], and aerosolization of SARS-CoV-2 could be a barrier to catheter hygiene and maintenance [7]. Finally, the pandemic has revealed staffing constraints and supply chain weaknesses that limit the ability of microbiology labs and infectious disease specialists to fully support infection prevention and antimicrobial stewardship policies, which also may affect BSI rates and outcomes [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Considering this situation, regional laboratories implemented molecular areas to expand diagnostic capacity beyond these main centers [7]. The literature describes the adaptation of COVID-19 diagnosis in Microbiology departments with previous experience in PCR-performing [1,4,8] and also in laboratories from low-resource countries [9]. However, to the best of our knowledge, there is no work describing the creation of a molecular area from scratch in the context of the COVID-19 emergency in a regional hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Since Nucleic Acid Amplification Techniques (NAAT), based on real-time RT-PCR (RT-qPCR), are the main tools for the detection of SARS-CoV-2, the diagnosis was initially centralized at reference hospitals, with well-equipped microbiology departments and qualified staff [2,3]. Within a few weeks, new technology was introduced, additional diagnostic circuits were created and trained staff were incorporated, reinforcing work shifts [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few studies on the impact of SARS-CoV-2 testing on other diagnostic tests. One Spanish study, from a more general microbiology laboratory, covering the early part of the pandemic (2019–2020), demonstrated a massive rise in the number of virology tests, without breaking these down into those for specific viruses [ 22 ]. Our study covering a longer period before and during the pandemic (2018–2022), focusing on just virology testing, is therefore a useful complementary study to this one.…”
Section: Discussionmentioning
confidence: 99%